1996
DOI: 10.1111/j.1475-2743.1996.tb00531.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of exchangeable potassium on soil erodibility

Abstract: Regular application of slurry manurc in large quantities is thought to degrade soil structure and increase erodibility. One hypothesis links this to the large input of potassium which increases the exchangeable potassium percentage (EPP) and, thereby, dispersion. The effect of EPP on erodibility was quantified in three experiments. In the laboratory, eleven rainfall experiments were conducted using a silty topsoil from a typic Hapludalf which was fertilized to EPPs of 4 to WYO. Field rainfall experiments on 22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 11 publications
1
19
0
4
Order By: Relevance
“…According to them, underlying this was the interlayer adsorption of K on clay surfaces at low EPP resulting in the stabilisation of micro aggregates (Auerswald et al, 1996), and clay dispersion resulting in structure destabilisation at large EPP (Chen et al, 1983). The latter is consistent with the findings of several researchers who have reported that clay dispersion results in a reduction in K s (Levy et al, 1998;Keren and Ben-Hur, 2003).…”
Section: Sdc (%)supporting
confidence: 74%
See 1 more Smart Citation
“…According to them, underlying this was the interlayer adsorption of K on clay surfaces at low EPP resulting in the stabilisation of micro aggregates (Auerswald et al, 1996), and clay dispersion resulting in structure destabilisation at large EPP (Chen et al, 1983). The latter is consistent with the findings of several researchers who have reported that clay dispersion results in a reduction in K s (Levy et al, 1998;Keren and Ben-Hur, 2003).…”
Section: Sdc (%)supporting
confidence: 74%
“…Khan and Afzal (1990) found that the saturated hydraulic conductivity (K s ) is affected by the amount of exchangeable Na, which was explained by the fact that Na reduces soil pore sizes through increasing the diffuse double layer thickness and creating repulsion forces among clay particles. High concentrations of hydrated Na and K cause clay dispersion, resulting in reduced infiltration rate, earlier/increased runoff, and increased sediment concentrations (Auerswald et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulation of K in the surface soil of manured soils has been reported (Hao and Chang 2003;Olson et al 2003). High K may contribute to increases in soil salinity (Liebhardt and Shortall 1974), may interfere with crop uptake of other nutrients such as Mg and Ca (Callan and Westcott 1996), and may contribute to decreases in hydraulic conductivity (Shainberg 1995) and increases in soil erodibility (Auerswald et al 1996). However, as noted above, Miller et al (2000) found no evidence of reduced saturated hydraulic conductivity and unsaturated hydraulic conductivity at -0.3 kPa potential in manured treatments compared with the control treatment.…”
Section: Discussionmentioning
confidence: 82%
“…P from agricultural land enters ground and surface waters mainly by erosion, surface runoff and leaching, causing eutrophication (Ö born et al 2005b;Prasuhn and Sieber 2005). Heavy K fertilizer dressings may increase soil dispersion and thus reduce infiltration, which in turn increases soil erodibility (Auerswald et al 1996). P and K soil contents of agricultural land rise due to overfertilization (Bach and Frede 1998;Jakobsen 1993;Withers et al 2001).…”
Section: Introductionmentioning
confidence: 99%